2009
DOI: 10.1002/mana.200610757
|View full text |Cite
|
Sign up to set email alerts
|

On the expected surface area of the Wiener sausage

Abstract: For parallel neighborhoods of the paths of the d-dimensional Brownian motion, so-called Wiener sausages, formulae for the expected surface area are given for any dimension d ≥ 2. It is shown by means of geometric arguments that the expected surface area is equal to the first derivative of the mean volume of the Wiener sausage with respect to its radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Recently it was shown that, as expected, the mean surface area of the Wiener sausage satisfies (see [4], [5])…”
Section: Introductionsupporting
confidence: 64%
“…Recently it was shown that, as expected, the mean surface area of the Wiener sausage satisfies (see [4], [5])…”
Section: Introductionsupporting
confidence: 64%
“…Proof. Rataj et al in [18], theorem 3.3, showed that V ′ A (t) exists for every t ≥ diam(A), thus we have for every t ≥ diam(A)…”
Section: The Preceding Theorem Is Still Valid If One Replaces B Nmentioning
confidence: 75%
“…as l → ∞ due to the integrability of γ 2 11 . The following statement gives a sufficient condition for (36).…”
Section: Preliminary Results From Linear Regressionmentioning
confidence: 99%
“…Corollary 3.6. If Q l = σ 2 I l for some σ > 0, where I l is the identity matrix, then condition (36) in Theorem 3.5 is satisfied for all t = 0 provided that…”
Section: Preliminary Results From Linear Regressionmentioning
confidence: 99%
See 1 more Smart Citation